An Overview of Reading a Narrative Text and the Application of Reciprocal Teaching Strategy - Ardiya Ardiya (Jurnal Pendidikan Teknologi Informatika dan Sains, 2019)
This article aims to explain the conceptualization of reading texts and the use of narrative texts in learning English by using a literature review method on reading theory, narrative text theory and reciprocal learning theory. One strategy that can be used in narrative text learning is reciprocal learning strategies. The search results on the theory and application of reciprocal learning strategies show that reciprocal learning has several advantages, namely student participation increases in class, students are more active, students enjoy collaboration in class, and students have more responsibility for themselves and classmates. Even in terms of interpersonal communication skills, students are more active in using English in class. Thus, it can be concluded that reciprocal learning strategies are very suitable for narrative text learning.